2000
DOI: 10.1507/endocrj.47.481
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Luteinizing Hormone-Releasing Hormone-Stimulated Adrenocorticotropic Hormone Secretion in a Patient with Pituitary Hyperplasia due to Primary Hypothyroidism.

Abstract: Abstract.We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…The literature search yielded 649 potentially relevant articles, spanning from January 1996 to December 2023. Following the removal of duplicates and the review of titles, abstracts, and full-length articles, we identified 55 articles [ 6 , 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ,…”
Section: Resultsmentioning
confidence: 99%
“…The literature search yielded 649 potentially relevant articles, spanning from January 1996 to December 2023. Following the removal of duplicates and the review of titles, abstracts, and full-length articles, we identified 55 articles [ 6 , 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ,…”
Section: Resultsmentioning
confidence: 99%